KEUNIKAN STRUKTUR BAHASA AL-QUR’AN DALAM ANALISIS I’JÃZ AL-BAYÃNI - Chindi Sri Hariyati; Tasyah Ardany Hasibuan, Esha Daffa Fathansyach, Harun Alrasyid (ADISAM PUBLISHER, 2024)
This study explores the uniqueness of linguistic structure in the Qur’an through the analysis of the concept of I’jãz Al-Bayãni. It focuses on the linguistic aspects of the Qur’an, particularly the unique sentence structures and styles of language. The aim of this research is to uncover the linguistic marvels of the Qur’an and understand how the concept of I’jãz Al-Bayãni is applied as an analytical method. Data collection methods involve literature review of the Qur’an and related studies. The findings of the research reveal that the Qur’an possesses unparalleled linguistic uniqueness, with remarkable rhetorical and aesthetic qualities. The novelty of this research lies in the application of the concept of I’jãz Al-Bayãni in understanding the depth of the linguistic beauty and uniqueness of the Qur’an, providing deeper insights into the linguistic phenomena within the sacred text. Thus, this research contributes significantly to understanding the linguistic richness of the Qur’an and its relevance in linguistic and literary contexts.